Warming signals in temperate reef communities following more than a decade of ecological stability. Issue 1989 (21st December 2022) - Soler, G. A.; Edgar, G. J.; Barrett, N. S.; Stuart-Smith, R. D.; Oh, E.; Cooper, A.; Ridgway, K. R.; Ling, S. D.
Abstract : Ecosystem structure and function are increasingly threatened by changing climate, with profound effects observed globally in recent decades. Based on standardized visual censuses of reef biodiversity, we describe 27 years of community-level change for fishes, mobile macroinvertebrates and macroalgae in the Tasmanian ocean-warming hotspot. Significant ecological change was observed across 94 reef sites (5–10 m depth range) spanning four coastal regions between three periods (1992–95, 2006–07, 2017–19), which occurred against a background of pronounced sea temperature rise (+0.80°C on average). Overall, fish biomass increased, macroinvertebrate species richness and abundance decreased and macroalgal cover decreased, particularly during the most recent decade. While reef communities were relatively stable and warming was slight between the 1990s and mid-2000s (+0.12°C mean temperature rise), increased abundances of warm affinity fishes and invertebrates accompanied warming during the most recent decade (+0.68°C rise). However, significant rises in the community temperature index (CTI) were only found for fishes, invertebrates and macroalgae in some regions. Coastal warming was associated with increased fish biomass of non-targeted species in fished zones but had little effect on reef communities within marine reserves. Higher abundances of larger fishes and lobsters inside reserves appeared to negate impacts of 'thermophilization'.